2017
DOI: 10.15226/2473-2176/2/1/00112
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Status and Factors for Non- Vaccination in Children at a Tertiary Care Hospital

Abstract: Immunization is a very effective strategy to prevent against common infectious disease. The objectives of the study were to determine the immunization status and reasons for non-vaccination of children coming to Civil Hospital Sukkur. This cross-sectional study was conducted pediatric OPD at Civil Hospital Sukkur from January 1, 2013, to June 30, 2013. Parents of children under five years of age brought their child to Outpatient Department of Civil Hospital Sukkur for any illness were asked to participate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Gender variation is the next observed variable in this study. 16,17 Our study showed female gender is vulnerable for immunization default with p-value 0.001 and OR 2.084 with (95% CI 1.347 to 3.226) which is similar to the systematic review by Mathew Joseph L and Mugada V et al studies. 18,19 Residence proved no correlation for partial immunization in our study which was similar to Holipa et al study and Madhavi et al study at Kakinada, AP.…”
Section: Discussionsupporting
confidence: 88%
“…Gender variation is the next observed variable in this study. 16,17 Our study showed female gender is vulnerable for immunization default with p-value 0.001 and OR 2.084 with (95% CI 1.347 to 3.226) which is similar to the systematic review by Mathew Joseph L and Mugada V et al studies. 18,19 Residence proved no correlation for partial immunization in our study which was similar to Holipa et al study and Madhavi et al study at Kakinada, AP.…”
Section: Discussionsupporting
confidence: 88%
“…The determinants are mostly related to child parental determinants 12 . Many parents usually give up on the cycle of immunization as the parents are too busy to bring the child for vaccination 13 maternal education 14 and health seeking behavior of mothers 15 , compliance with interventions to increase the vaccination uptake by the health departments 16 ethnic, social determinants and poverty 17 , lack of parental information about immunization 18 lack of knowledge regarding the dangers of no immunization 15 lack of knowledge regarding the number of doses 13 child's gender as in Pakistan girls are least likely to obtain all elementary vaccines than boys 19 , distance between house to immunization facility 20 , parental lack of knowledge and unawareness of benefits of immunization 21 , and incorrect ideas about vaccination were also significant for fail immunization coverage 22 .…”
Section: Introductionmentioning
confidence: 99%